Analysis of the Perspective on Pension Fund Management: From Pay-As-You-Go to Fully Funded Systems - Astuthy, Ritma Tri; Ulfah, Alitha; Tenriwaru, Tenriwaru (Contemporary Journal on Business and Accounting, 2024)
Purpose – The aim of this research is to examine the implementation of pension fund management through a fully funded scheme in the civil servant pension system in Indonesia. Design/methodology/approach – This research is designed using literature and journal review methods. The methodology involves selecting and collecting relevant data from literature and performing data analysis related to the implementation of the fully funded pension scheme. Findings – The research finds that Indonesia's government is not yet prepared to implement the fully funded pension scheme for civil servants, with significant gaps in regulatory frameworks and the need for improvements in pension fund management, participant contributions, and risk management. Originality – The originality of this research lies in its evaluation of Indonesia's readiness to implement a fully funded pension scheme for civil servants, as well as its identification of regulatory gaps and the need for improvements that have not been addressed in previous studies. Keywords: Pay as you Go, Fully Funded Paper Type Research Result